1995
DOI: 10.1111/1523-1747.ep12606239
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline Inhibits T-Cell Adherence to Keratinocytes

Abstract: In many inflammatory dermatoses leukocyte function-associated antigen-1/intercellular adhesion molecule-1 mediated T-cell/keratinocyte adhesion is considered to play an important role. Pentoxifylline (PTX), a methylxanthine derivative widely used for the symptomatic treatment of various vascular disorders, was recently found to have anti-inflammatory effects. PTX can suppress tumor necrosis factor-alpha production and function, and inhibits leukocyte-endothelial cell adherence. The aim of the present study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Kovach et al has shown that PTX can inhibit integrin mediated adherence of IL-2 activated PBLs to HUVECs, matrix components and cultured tumor cells. 32 Studies by other groups have shown that PTX can inhibit the adhesion of T cells to keratinocytes 33 and endothelioma cells. 34 Our study shows that the inhibition in adhesion of F10 cells to ECM components was evident only up to four hours and further incubation with the drug for 24 hours in fact brought about a significant increase in adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Kovach et al has shown that PTX can inhibit integrin mediated adherence of IL-2 activated PBLs to HUVECs, matrix components and cultured tumor cells. 32 Studies by other groups have shown that PTX can inhibit the adhesion of T cells to keratinocytes 33 and endothelioma cells. 34 Our study shows that the inhibition in adhesion of F10 cells to ECM components was evident only up to four hours and further incubation with the drug for 24 hours in fact brought about a significant increase in adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of circumstantial evidence, it has been revealed that thymic cortical epithelial cells form a web or network that makes close contact with immature (CD4 and CD8 double-positive) T-lymphocytes undergoing positive selection. Interaction of T-lymphocytes with epidermal keratinocytes has also been reported (Singer et al, 1990;Stoof et al, 1992;de Haan et al, 1994;Bruynzeel et al, 1995). It was speculated that such interactions may play a critical role for the extrathymic or post-thymic events in T-lymphocyte maturation (Parker et al, 1990).…”
Section: Do Lymphocytes Interact Withmentioning
confidence: 93%
“…PTX also downregulates the expression of adhesion molecules in human keratinocytes, T lymphocytes and epidermal Langerhans cells [15, 17, 18, 28]. Hydroxyl radical scavenger properties have also been described for PTX [22].…”
Section: Commentmentioning
confidence: 99%
“…Besides its hemorheologic activity, PTX has been found to suppress the production of TNF-α by murine and human leukocytes [14, 15, 16]. Moreover, recent reports have described that PTX inhibits T-cell adherence to keratinocytes and the activation of human T lymphocytes [17, 18]. Therefore, considering these anti-inflammatory effects, we assessed the clinical efficacy of PTX for the treatment of AP patients while measuring its effects on erythema, papules and nodules as well as on the improvement of pruritus.…”
Section: Introductionmentioning
confidence: 99%